The Role of Islamic Psychology In Improving Self-Transcendence and Faith - Ghozali, Ghozali (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2023)
A research conducted by Leuba (1925) mentioned that the religious level of psychologists are at the lowest level in compared with academic`s circles in other scholarly fields. This is due to the paradigm of positivism that tends to eliminate radically the metaphysical dimension of psychic. As the result they could not understand the meaning of religiousness.On the other hand, there is a paradigm of Islamic psychology which is currently growing rapidly which has an integral character, both at the level of ontological, epistemological, axiological and methodological. Thus, Islamic psychology is considered capable of answering the psychological and theological moslems phenomenon at the same time. This research tries to express the teological dimensions of Islamic psychology as well as it role in improving the faith and self transcendence. The methodology that used in this research was the library research with the descriptive analysis approach. The result of this study indicates that the Islamic psychology have at least tree important roles in improving the faith and self transcendence. First, Islamic psychology has a theological dimension that serves as media that is most representative to knowing the God (The immanent). Second, as science Islamic psychology has four functions to improving the faith and self transcendence, namely: ta`rif al-nafs (description), tarbiya al-nafs (pedagogical and prevention), muraqaba al-nafs (rehabilitation), and taqwimal-nafs (prediction). Third, ma`rifat al-nafs (knowledge of al-nafs), could strengthen the roots of individual faith. Fourth, Islamic psychology has a role in growing self transcendence which is theoanthropocentric oriented.